Archenemies - Meyer, Marissa (New York : Feiwel and Friends, 2018)
Nova and Adrian fought the battle of their lives against the Anarchist known as the Detonator. It was a short-lived victory-- the Anarchists still have a secret weapon. And Nova's double life is getting more complicated: as Insomnia, she is a member of the Renegades; as Nightmare, she is an Anarchist. And Adrian has some secrets of his own. Together they can save the world... but time is running out....--
Keywords: Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Revenge -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Action and adventure fiction.2lcgft